INTERNAL AND EXTERNAL FACTORS AFFECTING AUDITOR’S ABILITY IN DETECTING FRAUDULANCE FROM THE ACCOUNTING STUDENT’S PERSPECTIVE - Liong, Jhun; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
In assessing financial information, auditors are required to be able to identify fraud to support the creation of transparency and accountability. Many recent financial statement fraud cases have demonstrated the auditor's failure to spot fraud. From many cases occurred and studies that have not yet provided a definite answer regarding the factors influencing an auditor's ability to detect fraud, this research paper was formed to examine the impact of professional scepticism, auditor competence, and red flags towards the auditor's ability to detect fraud as the dependent variable from the viewpoint of accounting students currently enrolled in college or have studied auditing through questionnaire. The sampling method conducted in this research is the non-parametric sampling method, specifically simple random sampling, which would then be processed using SPSS for descriptive statistics and PLS for model testing. The 197 questionnaires obtained and processed showed that each indicator was able to describe the variables used, the PLS model was able to provide pretty good predictions of the model, and each independent variable was able to provide a significant positive influence on its dependent variable. Therefore, in fraud detection, an auditor must always question the most minor thing in his findings, improve his ability to analyze the possibility of fraud occurring, and catch warning signs that often appear minor.